Depression, A Mental Aspect in Rheumatoid Arthritis Comorbidities - Birgitta Fajarai (Scientia Psychiatrica, 2022)
Rheumatoid arthritis (RA) significantly impacts patients' mental health, especially in generating depression. It is affected by RA clinical presentations of deformities, pain, and disability that significantly affect patient quality of life and become a stressor to mental comorbidities. Clinicians and society often overlook mental issues related to a disease, including patients and their families. Mental issues, especially depression, have become a global burden for people of all ages. This review presents the recent study of depression as a comorbid to rheumatoid arthritis patients. Recent studies correlate depression with increased RA progressivity that is mediated by inflammation mechanisms. Through this mechanism, the RA progressivity affects the occurrence of depression, but also, the depression worsens the RA symptoms. Although most RA therapy help reducing depression, a few do the opposite. Some of the assessment has been developed in helping clinicians evaluate RA disease activity and depression early. The understanding dan awareness of the bidirectional mechanism will help clinicians improve the management of rheumatoid arthritis and depression.